2010
DOI: 10.1007/s10494-010-9314-z
|View full text |Cite
|
Sign up to set email alerts
|

Large Eddy Simulation of a Controlled Diffusion Compressor Cascade

Abstract: In this research a Controlled Diffusion (CD) compressor cascade stator blade is simulated at a Reynolds number of ∼ 700, 000, based on inflow velocity and chord length, using Large Eddy Simulation (LES). A wide range of flow inlet angles are computed, including conditions near the design angle, and at high negative and positive incidence. At all inlet angles the surface pressure distributions are well-predicted by the LES. Near the design angle the computed suction side boundary layer thickness agrees well wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…It is often assumed that streamwise vorticity of this kind is confined to concave pressure surfaces. Examples of streamwise vorticity appearing on the convex surfaces of blades [9] and circular cylinders [10] have been observed both experimentally and computationally. The authors have observed streamwise vorticity on suction surfaces, both experimentally [4] and computationally [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is often assumed that streamwise vorticity of this kind is confined to concave pressure surfaces. Examples of streamwise vorticity appearing on the convex surfaces of blades [9] and circular cylinders [10] have been observed both experimentally and computationally. The authors have observed streamwise vorticity on suction surfaces, both experimentally [4] and computationally [9].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of streamwise vorticity appearing on the convex surfaces of blades [9] and circular cylinders [10] have been observed both experimentally and computationally. The authors have observed streamwise vorticity on suction surfaces, both experimentally [4] and computationally [9]. In this paper, examples of streamwise and crossflow vorticity on [4] convex surfaces will be considered.…”
Section: Introductionmentioning
confidence: 99%
“…A theory giving expected spanwise wavelengths for a circular cylinder was developed by Kestin and Wood 9 in 1970. "Streaky structures" and streamwise vortices have been observed and predicted on flat plates 10 , on compressor blades 11,12 and on the convex surface of a supercritical airfoil, following an initial concave surface exhibiting Görtler vorticity 13 . In a study of plane shear layers, Lasheras et al 14 have concluded that these are unstable to three-dimensional perturbations in the upstream conditions.…”
Section: Introductionmentioning
confidence: 97%
“…With the enormous development in computer science, the large eddy simulation (LES) method has been used in compressor cascade flow simulation in recent years, utilizing a large amount of computer resources (Matsuura & Kato, 2007;McMullan & Page, 2011;Teramoto, 2005;Zaki, Wissink, Durbin, & Rodi, 2009). Modeling threedimensional corner separation requires the CFD code to be very robust.…”
Section: Introductionmentioning
confidence: 99%